2018
DOI: 10.1021/acs.biomac.8b00578
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Mucoadhesive Spider Silk

Abstract: Mucoadhesion is defined as the adhesion of a material to the mucus gel covering the mucous membranes. The mechanisms controlling mucoadhesion include nonspecific electrostatic interactions and specific interactions between the materials and the mucins, the heavily glycosylated proteins that form the mucus gel. Mucoadhesive materials can be used to develop mucosal wound dressings and noninvasive transmucosal drug delivery systems. Spider silk, which is strong, biocompatible, biodegradable, nontoxic, and lightwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Thereby, recombinant CYS domain delivery could help to determine the minimal amount of recombinant protein necessary to reinforce the colonic mucus with aim to limit diffusion of macromolecules and toxins in mucus as observed for the delivery of lipids 59 . Reinforcing mucus hydrogels is an attractive approach which can be achieved through the delivery of recombinant molecules 60 or by administering recombinant probiotics that would secrete molecules made of CYS domains. This strategy could help in reducing the bacterial burden in the context of mucus-associated diseases, such as ulcerative colitis 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, recombinant CYS domain delivery could help to determine the minimal amount of recombinant protein necessary to reinforce the colonic mucus with aim to limit diffusion of macromolecules and toxins in mucus as observed for the delivery of lipids 59 . Reinforcing mucus hydrogels is an attractive approach which can be achieved through the delivery of recombinant molecules 60 or by administering recombinant probiotics that would secrete molecules made of CYS domains. This strategy could help in reducing the bacterial burden in the context of mucus-associated diseases, such as ulcerative colitis 61 .…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, SELPs containing arginine (R), lysine (K), glutamic acid (E), and cysteine (C) substitutes were selected for investigation as possible designs for mucoadhesive delivery systems, as these proteins contain charged groups and thiol groups resulting from the selected modification of the elastin "X" amino acid. Many studies have demonstrated the importance of electrostatic interactions in mucoadhesion [9,19,43,44]. Additionally, mucoadhesive nanoparticle drug delivery systems containing thiol groups have resulted in increased retention because of the propensity for disulfide bond formation with mucins containing thiol groups [44,45].…”
Section: Evaluation Of Selp Nanoparticle Mucoadhesive Propertiesmentioning
confidence: 99%
“…Despite the diverse and dynamic microenvironment, the mucosal surface provides numerous physical and chemical features that can be exploited to increase mucoadhesion of carrier particles in drug delivery systems [6][7][8]. These approaches include particles with tailored hydrogen-bonding, electrostatic interactions, hydrophilicity, thiolation, and specific binding to mucins, as well as precise control over size and shape of the substrate [9][10][11][12][13][14][15]. Numerous mucoadhesive designs have been developed to improve retention of particles in mucus membranes, such as lipids [16], lectins [17], chitosan [18], synthetic polymers [19], and other biopolymers [9,20] in the form of adhesive tablets [21], micro-and nanoparticles [22], films [23], nanogels [24], and sprays [25].…”
Section: Introductionmentioning
confidence: 99%
“…Production of proteins in heterologous systems also comes with the benefit of allowing modifications of the produced proteins, such as covalently incorporated functional motifs. [25][26][27][28][29][30] Hence, recombinant spider silk fibers could both provide physical guidance for sprouting neurites as has been described for the native fiber, and be decorated with cell binding motifs providing signals that promote neurite extension. In addition to the relatively straightforward and feasible manufacturing process of recombinant spider silk fibers, such a scaffold would potentially outcompete those made from, for example, vitronectin only since it cannot be spun into fibers and likely be more flexible and bioactive compared to fibers manufactured from synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical point of view, however, recombinant spider silk would be superior to the natural fiber since it is of non‐animal origin and contains only a single defined protein in contrast to the natural fiber that is composed of many different proteins. Production of proteins in heterologous systems also comes with the benefit of allowing modifications of the produced proteins, such as covalently incorporated functional motifs 25–30 . Hence, recombinant spider silk fibers could both provide physical guidance for sprouting neurites as has been described for the native fiber, and be decorated with cell binding motifs providing signals that promote neurite extension.…”
Section: Introductionmentioning
confidence: 99%